A metabolomic strategy revealed the role of JA and SA balance in Clematis terniflora DC. Response to UVB radiation and dark. Issue 2 (8th February 2019) - Yang, Bingxian; Chen, Meng; Wang, Tantan; Chen, Xi; Li, Yaohan; Wang, Xin; Zhu, Wei; Xia, Li'an; Hu, Xingjiang; Tian, Jingkui
Abstract : Clematis terniflora DC. is a valuable resource with potential high pharmaceutical value. Proteomic, transcriptomic and metabolomic analyses of C. terniflora that has been exposed to high levels of UVB irradiation and dark conditions (HUVB + D) have revealed the mechanisms underlying its medicinal potential. However, the signal transduction pathways and the mechanisms of regulation for the accumulation of secondary metabolites remain unclear. In this study, we show that the jasmonic acid (JA) and salicylic acid (SA) signals were activated in C. terniflora in response to HUVB + D. Metabolomic analysis demonstrated that the perturbation in JA and SA balance led to additional reallocation of carbon and nitrogen resources. Evaluating the fold change ratios of differentially changed metabolites proved that JA signal enhanced the transformation of nitrogen to carbon through the 4‐aminobutyric acid (GABA) shunt pathway, which increased the carbon reserve to be utilized in the production of secondary metabolites. However, SA signal induced the synthesis of proline, while avoiding the accumulation of secondary metabolites. Over all, the results indicate that the co‐increase of JA and SA reconstructed the dynamic stability of transformation from nitrogen to carbon, which effectively enhanced the oxidative defense to HUVB + D in C. terniflora by increasing the secondary metabolites.